Respostas

2014-04-29T08:56:16-03:00
1)x= -b +-raiz quadrada b² -4ac / 2a 
x = -3 +-v9+40/20
x = -3 +-7/20
x´= 4/20 = 1/5
x´´ = -10/20 = -1/2
2) -b +-raiz quadrada b² -4ac / 2a 
-2 +-v4+32 / 2
x = -2 +-6 / 2
x´= 4/2 = 2
x´´ = -8/2 = -4

3)
x= 3 +- v9+16/2
x = 3+-5/2
x´= 8/2 = 4
x´´ = -2/2 = -1

4)
x= -10 + -v100-84/ 14
x= -10 +-4/14
x´= -6/14 = -3/7
x´´ = -14/14 = -1

5)
x = -6 +-v36+0 / -8
x = -6+-6/-8
x´= 0/-8 = 0
x ´´ = -12/-8 = 3/2

6)
r² = 16
r = v16
r = +-4

7)
x= -1 +-v1+24 / -12
x = -1 +-5 / - 12
x´= 4/-12 = -1/3
x´´ = -6/-12 = 1/2

8)x= 10+-v100+0/10
x= 10+-10/10
x´= 20/10= 2
x´´ = 0/10 = 0